(untitled) (Circe de clásicos y modernos, 2018)
In this paper we offer the translation from Latin to Spanish of Ramón Llull ́s Liber de convenientia fidei et intellectus in obiecto (1314) with introduction and notes. This is a work where the mallorcan philosopher makes a synthetic framework of his thinking on the relationship between faith and reason, as well as of his position towards the defense of catholic faith and conversion of non-christian people. The text, which is shown as a definitive work in the setting of this rela-tionship, uses the most characteristic principles of his system, Ars magna, but still is a rara avis inside the opus lulliana: is full of biblical quotations and allusions to the most renowned ecclesiastical auctoritates, all these absents in most lullian woks.